Biosystems and their structural and functional representations in industrial product design (Journal of the College of Basic Education, 2023)
The research examines the characteristics and variables of Biosystems according to their structural and surface features, based on an explanation of what their nature is according to the variables of chemical conversion of energy, the multifunctional properties of plant leaves, water resistance in insects, dry adhesion, low hydrodynamic drag, and aerodynamics. (6) models were selected as a sample for analysis. A number of results were reached, all of which were a careful analysis of the structural and performance variables of the models. Hence, a number of conclusions were reached that provided an analytical picture of the importance and role of Biosystems in expanding the frameworks of design knowledge.